1D Sub‐Nanotubes with Anatase/Bronze TiO2 Nanocrystal Wall for High‐Rate and Long‐Life Sodium‐Ion Batteries. Issue 46 (8th October 2018) - Chen, Biao; Meng, Yuhuan; Xie, Fangxi; He, Fang; He, Chunnian; Davey, Kenneth; Zhao, Naiqin; Qiao, Shi‐Zhang
Abstract: The development of 1D nanostructures with enhanced material properties has been an attractive endeavor for applications in energy and environmental fields, but it remains a major research challenge. Herein, this work demonstrates a simple, gel‐derived method to synthesize uniform 1D elongated sub‐nanotubes with an anatase/bronze TiO2 nanocrystal wall (TiO2 SNTs). The transformation mechanism of TiO2 SNTs is studied by various ex situ characterization techniques. The resulting 1D nanostructures exhibit, synchronously, a high aspect ratio, open tubular interior, and anatase/bronze nanocrystal TiO2 wall. This results in excellent properties of electron/ion transport and reaction kinetics. Consequently, as an anode material for sodium‐ion batteries (SIBs), the TiO2 SNTs display an ultrastable long‐life cycling stability with a capacity of 107 mAh g −1 at 16 C after 4000 cycles and a high‐rate capacity of 94 mAh g −1 at 32 C. This a high‐rate and long‐life performance is superior to any report on pure TiO2 for SIBs. This work provides new fundamental information for the design and fabrication of inorganic structures for energy and environmental applications. Abstract : 1D elongated sub‐nanotubes with an anatase/bronze TiO2 nanocrystal wall are synthesized through a gel‐derived method. This new structure exhibits a high aspect ratio, open interior, and an anatase/bronze nanocrystal wall, that results in fast electron/Na + transport and large storage sites. This work enables new paths to the design and fabrication of inorganical structures for energy and environmental applications.